(untitled) (Research, Society and Development, 2021)
One of the challenges for developers and software development companies is the implementation of source codes in a standardized way. To assist in this process, there are some design patterns that provide directions such as software reuse. In this sense, this study aimed to assess the behavior of developers during the implementation of a software reuse support tool. The evaluation was carried out through the application of questionnaires before and after the implementation of the software reuse support tool. After performing the analysis of the questionnaires, it can be seen that the developers understand the concept of software reuse. However, they use the tool inappropriately. With this, it is clear the need for a commitment from the entire developer team together with the project managers.